2020
DOI: 10.13057/biodiv/d211061
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Investigating environmental impacts of long-term monoculture of sugarcane farming in Indonesia through DPSIR framework

Abstract: Abstract. Putra RP, Ranomahera MRR, Rizaludin MS, Supriyanto R, Dewi VAK. 2020. Short Communication: Investigating the environmental impacts of long-term monoculture of sugarcane farming in Indonesia through DPSIR framework. Biodiversitas 21: 4945-4958. An increasing trend of sugar demand in Indonesia due to the rising population has forced the government to boost its national sugarcane production through intensification program. Long-term monoculture system has long been practiced by sugarcane growers in Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 111 publications
(175 reference statements)
1
9
0
2
Order By: Relevance
“…Green cane harvesting-trash blanketing (GCTB) is an agronomic practice of returning sugarcane residues, i.e., dry leaves, left cane shoots, and the remaining sugarcane stalks back to the field after the harvesting process, as an in-situ organic matter (OM) source (Tórtora et al 2013). The residues will be decomposed and being a source of organic matter (Putra et al 2020). Carvalho et al (2017) suggested that the positive impacts of implementing a trash blanket can be attained when at least seven tons per hectares of sugarcane residues are preserved on the soil surface.…”
Section: Green Cane Harvesting-trash Blanketing (Gctb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Green cane harvesting-trash blanketing (GCTB) is an agronomic practice of returning sugarcane residues, i.e., dry leaves, left cane shoots, and the remaining sugarcane stalks back to the field after the harvesting process, as an in-situ organic matter (OM) source (Tórtora et al 2013). The residues will be decomposed and being a source of organic matter (Putra et al 2020). Carvalho et al (2017) suggested that the positive impacts of implementing a trash blanket can be attained when at least seven tons per hectares of sugarcane residues are preserved on the soil surface.…”
Section: Green Cane Harvesting-trash Blanketing (Gctb)mentioning
confidence: 99%
“…Crop diversification offers several benefits, but this practice is not yet popular and being implemented by Indonesian sugarcane growers (Putra et al 2020). They may be indolent in applying intercropping since the positive impacts cannot be seen immediately after its implementation.…”
Section: Crop Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradasi kesuburan tanah merupakan salah satu faktor krusial yang berkontribusi terhadap penurunan produktivitas tebu di Indonesia. Beberapa wilayah di Indonesia, penanaman tebu dilakukan secara monokultur dalam jangka waktu lama, bahkan hingga puluhan tahun (Putra et al 2020). Dari proses pemanenan tebu di lapang, terdapat beberapa jenis residu, antara lain daun kering (daduk) maupun daun hijau, sogolan atau tunas tebu muda, pucuk tebu, serta batang tebu hasil tebangan yang tertinggal di lahan (Karve et al 2001;Misran 2005).…”
Section: Pendahuluanunclassified
“…), maize (Zea mays L.), sugarcane (Saccharum officinarum L.), and fuel crops such as rapeseed (Brassica napus L.) take up space instead of multicultural food crops resulting in adverse impact leading to loss of soil fertility, increased soil salinity, erosion, depletion, and decreased environmental quality and biodiversity soil depletion (Ghadeer and Al Khalil, 2019;Guillaume et al, 2016;Mohamed et al, 2016;Putra et al, 2020;Schiefer et al, 2016;Vanham et al, 2021). In particular, several experts have discussed the problem of soil fertility in oil palms in Indonesia (Herry et al, 2020;Hsiao-Hang et al, 2016;Petrenko et al, 2016;Shahputra and Zen, 2018), while other scientists (Hartemink, 1964;Kusumawati et al, 2020;Putra et al, 2020) have discussed and reported about soil degradation in sugarcane plantations in Indonesia. Furthermore, climate change predictions point at more frequent environmental instabilities such as extensive heat resulting in dryness and natural fires, excessive precipitation leading to floods, sudden and intense cold bringing crop yield loss.…”
Section: Introductionmentioning
confidence: 99%